Gringo in Mañanaland: Latin America in Hollywood - Reich Corseuil, Anelise (Revista Interfaces, 2020)
ABSTRACT: This article presents an analysis of Gringo in Mañanaland, a 1995 documentary by the American media activist and producer DeeDee Halleck. This documentary offers a revisionist perspective about the US representations of Latin America especially by Hollywood films. Thus, Halleck’s production is representative of the reflexive aesthetics of contemporary documentary production. Such aesthetics is revealing of a fruitful political, economic and cultural debate, as an alternative to the commercial film production. As support for the discussion of Gringo in Mañanaland as a revisionist documentary, this analysis relies on the studies about Hollywood films and their representations of Latin America by Robert Burgoyne, Tunico Amancio and David Bordwell, as well as on Robert Rosenstone’s studies on film as tools to revision of history.